The sacrality of the secular: postmodern philosophy of religion - Onishi, Bradley B. (Columbia University Press, 2018)
Introduction: Philosophy's "turn to religion" and secularities beyond secularism -- Different worlds: Weber, Heidegger, and the meaning of life -- Philosophizing with religion: Secular reenchantment in the early Heidegger -- Excendence and heterology: religious and secular in interwar Paris -- A prophet of the impossible: Batailee's mystical turn and continental philosophy of religion -- The sacrality of the secular: on the history and end of philosophy of religion - Conclusion: /Contemporary philosophy of religion and religious studies: three examples